MODEL JIGSAW DALAM PERKULIAHAN PENGANTAR ILMU EKONOMI UNTUK MENINGKATKAN KEMANDIRIAN DAN PRESTASI MAHASISWA - Dewi Kusuma Wardani; Leny Noviani (PAEDAGOGIA, 2010)
The aim of this research is to apply the Jigsaw's model on subject PengantarIlmu Ekonomi at Economic departement of FKlP in Sebelas Maret University to increaseindependent learning and stu-dent achievement. Method used in this research isClassroom Action Research (CAR). According to CAR principles there are research cycles,where the number of research cycles depend on efficacy indicator achieved. In theresearch, the research cycles consist of fours steps, there are: planning, action execution,observation and reflextion. Result describe that learning by using Jigsaw model canimprove student independent learning. By having high independent learning the studentswill be more initiative, exploratary, creative; and have skills to express themself, trying toovercome problem, dare of what they were to be responsible doing; have the ability todescribe the opinion actively in lecturing and looking for experience learning. By havinggood independent learning level, the students can improve the existence of their learningresult. Students try to get information from various source, then to expostulate with otherstudents. These will improve understanding subjects which is inreturn will improve studentlearning achievement.